1987
DOI: 10.1121/1.395825
|View full text |Cite
|
Sign up to set email alerts
|

A method of range and depth estimation by modal decomposition

Abstract: Normal mode amplitudes are definite functions of depth and have a characteristic phase as a function of source range rs [i.e., exp(−ikirs), where ki is the ith mode wavenumber]. The range and depth of an acoustic source in the ocean can then be determined by decomposing array data and beamforming on the mode amplitudes. In particular, the product of the normal mode amplitudes with the steering vector Ui [where Ui=exp(ikir) ] is maximum for the true source range (r=rs). Similarly, the correlation of the measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
51
0

Year Published

1989
1989
2016
2016

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 145 publications
(51 citation statements)
references
References 0 publications
0
51
0
Order By: Relevance
“…Some of these methods include matched field processing which attempts to maximize an objective function which correlates the modeled and measured acoustic fields (Bucker, 1976;Baggeroer et al, 1988;Fawcett et al, 1996); modal decomposition methods which seek to match the modeled and measured modal amplitudes as a function of depth (Shang, 1985;Yang, 1987;Glattetre et al, 1989); matched mode methods which endeavor to match modeled and observed mode amplitudes as measured on a horizontal line array by use of the frequency-wavenumber (f-k) transform (Nicolas et al, 2006); and waveguide invariant approaches which are based on Chuprov's (1982) parameterization relating range and frequency to the slope of the striations in acoustic pressure in a frequency-range plot (Brekhovskikh and Lysanov, 1991;D'Spain and Kuperman, 1999). The waveguide invariant is commonly interpreted in terms of constructive and destructive interference of propagating normal modes (Turgut and Orr, 2010), but it has also been described in terms of ray theory (Gerstoft et al, 2001) and variations in eigenray arrival times (Harrison, 2011), and related to the wavenumber integration technique (Cockrell and Schmidt, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Some of these methods include matched field processing which attempts to maximize an objective function which correlates the modeled and measured acoustic fields (Bucker, 1976;Baggeroer et al, 1988;Fawcett et al, 1996); modal decomposition methods which seek to match the modeled and measured modal amplitudes as a function of depth (Shang, 1985;Yang, 1987;Glattetre et al, 1989); matched mode methods which endeavor to match modeled and observed mode amplitudes as measured on a horizontal line array by use of the frequency-wavenumber (f-k) transform (Nicolas et al, 2006); and waveguide invariant approaches which are based on Chuprov's (1982) parameterization relating range and frequency to the slope of the striations in acoustic pressure in a frequency-range plot (Brekhovskikh and Lysanov, 1991;D'Spain and Kuperman, 1999). The waveguide invariant is commonly interpreted in terms of constructive and destructive interference of propagating normal modes (Turgut and Orr, 2010), but it has also been described in terms of ray theory (Gerstoft et al, 2001) and variations in eigenray arrival times (Harrison, 2011), and related to the wavenumber integration technique (Cockrell and Schmidt, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…5 Equation (6a) is the same as the MMP ambiguity function evaluated at the source range 4 except for a slightly different shading coefficient. The depth z j where the ambiguity function is maximum yields the approximate source depth so long as the source depth is within the depth span of the VLA.…”
Section: T C Yang Andmentioning
confidence: 99%
“…(6) will approach E H mx b ð ÞA m ; and it still has the capability to resolve the source location. This mode conjugate formula is used in Matched Mode Processing (Yang, 1987;Yang, 1990). The principal criterion for ranging the source is phase conjugation, and the closure relation of the normal modes, i.e.,…”
Section: B Theoretical Expressionsmentioning
confidence: 99%
“…Shang (1985) and Shang et al (1985) recognized that the source range and depth can be determined from the phase difference between modes and the closure relation of normal modes, respectively. Yang (1987) utilized jointly the phase conjugation and the closure relation for normal mode beamforming to source locations, which can also be considered as Matched Mode Processing (MMP). Yang (1990) showed that when the sampled-mode-shape mode filter (Ferris, 1972) is used, MMP is equivalent to MFP.…”
Section: Introductionmentioning
confidence: 99%